Readiness Model of Micro, Small, and Medium Enterprises in the Creative Industry to Adopt Information Technology - Nikmatuniayah, Nikmatuniayah; Yudhaningsih, Resi; Handayani, Jati; Anugrahwati, Lilis Mardiana; Andrini, Nur Intan (PT Aksara Indo Rajawali, 2025)
The rapid development of IT in the era of Industry 4.0 has a significant impact on all digital transaction activities. The adoption of information technology (IT) can be studied from the perspective of user readiness. This study aims to examine the level of readiness of Micro, Small, and Medium Enterprises (MSMEs) in the creative industry in Semarang City in adopting IT. The research design and model were developed using the Technology Acceptance Model (TAM) and Technology Readiness Index (TRI). The population of the study was MSMEs in the creative industry in Semarang City, samples were taken using a non-probability procedure with a purposive sampling technique. The respondent data that could be processed amounted to 30 respondents. Data collection used a questionnaire survey method and was analyzed using the Partial Least Square (PLS) technique. The results showed that Optimism had a significant positive effect on Perceived Ease of Use and Perceived Usefulness. Innovativeness, Insecurity, and Discomfort had a positive but insignificant impact on Perceived Ease of Use and Perceived Usefulness. Perceived Ease of Use had an effect, and Perceived Usefulness did not affect Intention to Use IT.